Juvenile granulosa cell tumor associated with Ollier disease - Abhilasha Ashok Sampagar; Rahul R Jahagirdar; Vibha Sanjay Bafna; Sandip P Bartakke (Indian Journal of Medical and Paediatric Oncology)
Juvenile granulosa cell tumor (JGCT) is a rare neoplasm of childhood. Interestingly, it is known to be associated with Ollier disease, which is a rare bone disease characterized by multiple enchondromatosis. There is paucity of literature about the co-occurence of these two conditions. However, this association is noteworthy because these two conditions share a common pathogenesis. We report a case of JGCT in a 2.5-year-old female child in which multiple enchondromas mimicking bony metastasis were an incidental finding during routine workup for tumor staging, thus leading to a diagnosis of Ollier disease.